Voltage Control of Exchange Bias via Magneto-Ionic Approaches - Yifu Luo; Shengsheng Liu; Yuxin Li; Zhen Wang; Jie Zhang; Limei Zheng (Crystals)
The exchange bias (EB) effect denotes a magnetic bias phenomenon originating from the interfacial exchange coupling at the ferromagnetic/antiferromagnetic materials, which plays an indispensable role in the functionality of various devices, such as magnetic random-access memory (MRAM) and sensors. Voltage control of exchange bias offers a promising pathway to significantly reduce device power consumption, effectively fostering the evolution of low-energy spintronic devices. The “magneto-ionic” mechanism, characterized by its operational efficiency, low energy consumption, reversibility, and non-volatility, provides innovative approaches for voltage control of exchange bias and has led to a series of significant advancements. This review systematically synthesizes the research progress on voltage control of exchange bias based on the magneto-ionic mechanism from the perspectives of ionic species, material systems, underlying mechanisms, and performance parameters. Furthermore, it undertakes a comparative evaluation of the voltage-controlled exchange bias by different ions, ultimately providing a forward-looking perspective on the future trajectory of this research domain.